Blueprint - HOMESET Sdn Bhd : "HOMETRASH‟ / Aisa Ezzatulmirza Sapari - Sapari, Aisa Ezzatulmirza (2020)
HomeSet Sdn Bhd located in Jalan Prima Utama, Johor that focus on the production of smart dustbin which called as „homeTrash‟. „homeTrash‟ is an electronic machine to an improve normal dustbin by elevating it to be smart using sensors for garbage and logics. It functions to minimize human interferences in collection and disposal of trash. The company was started on January 2020 and focusing to targeted customer with certain stage of age especially for adults in range of 20 to 40, focusing to household and people who work in the offices especially to customer with middle-class income. As the beginning for the business, we will concentrate in peninsular Malaysia. Marketing of the product will be made through media social, online stores, banner, flyers and placement in the stores. „homeTrash‟ is a new product in Malaysia with combination of technology also design concept of decoration. The simple and small design make the product is easy to be place as a decoration where „homeTrash‟ has variation of colour that has a unique, streamlined design and also stainless steel. The selling of „homeTrash‟ is expected to start at the beginning of year 2021. The prediction of the total market size for three years is consistent by 45 %, where it will rise more in the future, although the market share and sales will grow by at least 4% for within three years. As agreed in our agreement, every partner contributed a certain amount of capital. We agreed that Aisa Ezzatulmirza Binti Sapari as a General Manager, Syafiqah Nureen Ezaty Binti Waharudin as Administrative Manager, Saidatul Afifah Binti Afpandi as the Marketing Manager, Alya Qistina Binti Hisyam as an Operational Manager, Zawani Najiah Binti Rasli as the Financial Manager and Nurzahirah binti Mohd Yussof as Sales Manager. Each partner has its own obligations where all partners are expected to plan and manage the department's operations wisely.